Comparison of the movement patterns between small- and large-sided game training and competition in professional soccer players - Giménez, J. V.; Del-Coso, J.; Leicht, A. S.; Gomez, M. Á. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The purpose of this investigation was to compare the movement patterns of professional soccer players during a small-sided game (SSG), a large-sided game (LSG), and a competitive friendly match (FM). METHODS: Fourteen professional players participated in three training routines with a similar relative pitch area per player. The SSG and LSG consisted of 8 repetitions of 4-min game play, interspersed by 2 minutes of active recovery, and their data were compared to the first 32 minutes of a FM. All movement patterns from walking to sprint running were recorded using 10-Hz GPS devices while player perception of exertion was recorded via visual analogue scale, post-trial. RESULTS: Total running distance (3852±405 vs. 3359±429 and 3088±414 m), running distance at 5-6.9 m/s (222±98 vs. 75±53 and 49±35 m) and maximal running speed (7.0±0.7 vs. 6.1±0.4 and 6.0±0.7 m/s) were significantly greater during FM than for SSG and LSG. However, the number of accelerations (462±16 vs. 458±12 vs. 422±15) and decelerations (733±31 vs. 692±24 vs. 609±27), and the rating of perceived exertion (8±1 vs. 7±1 vs. 5±1) were significantly greater during SSG compared to LSG and FM. CONCLUSIONS: Although smaller game-based training routines do not replicate exactly the movement patterns of a competitive match, they can increase the execution of short-term and high-intensity movements for specialized training in professional soccer players.